THE INFLUENCE OF COMPETENCE, ACCOUNTABILITY, MOTIVATION, AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF REGIONAL FINANCIAL MANAGERS IN SKPDS (REGIONAL WORK UNITS) OF BINJAI MUNICIPAL ADMINISTRATION - Hapsari, Nelly (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of competence, accountability, motivation, and organizational commitment on the performance of regional financial managers in SKPDs (Regional Work Units) of Binjai Municipal Administration. The research used quantitative analytic survey method by distributing questionnaires to regional financial managers in Binjai Municipal Administration. The population was financial managers in 33 SKPDs which consisted of PA (Budget Users), PPK (Financial Administrative Officials), and Treasurers of Expenditure (the total of 99 managers). The data were analyzed by using Descriptive Statistic Analysis and Partial Least Square Analysis (SEM-PLS) with Smart PLS software program. The result of the research showed that competence, accountability, motivation, and organizational commitment had positive and significant influence on the performance of regional financial managers.